2016
DOI: 10.1136/thoraxjnl-2015-207111
|View full text |Cite
|
Sign up to set email alerts
|

Historic air pollution exposure and long-term mortality risks in England and Wales: prospective longitudinal cohort study

Abstract: IntroductionLong-term air pollution exposure contributes to mortality but there are few studies examining effects of very long-term (>25 years) exposures.MethodsThis study investigated modelled air pollution concentrations at residence for 1971, 1981, 1991 (black smoke (BS) and SO2) and 2001 (PM10) in relation to mortality up to 2009 in 367 658 members of the longitudinal survey, a 1% sample of the English Census. Outcomes were all-cause (excluding accidents), cardiovascular (CV) and respiratory mortality.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 29 publications
5
31
2
1
Order By: Relevance
“…Beyond local social context, the only other aspects of place that have been examined in a long-term life-course framework are the influence of air pollution (Elliott et al, 2007) and residing in a rural context (Jokela et al, 2009). Hansell et al (2016, for example, combined data from members of the England and Wales Longitudinal Study with data on air pollution concentrations at residence in 1971, 1981, 1991 and 2001 to examine the contribution of long-term air pollution exposure to mortality (all-cause [excluding accidents], cardiovascular and respiratory mortality).…”
Section: Longitudinal Approaches To Examining Health and Place Acromentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond local social context, the only other aspects of place that have been examined in a long-term life-course framework are the influence of air pollution (Elliott et al, 2007) and residing in a rural context (Jokela et al, 2009). Hansell et al (2016, for example, combined data from members of the England and Wales Longitudinal Study with data on air pollution concentrations at residence in 1971, 1981, 1991 and 2001 to examine the contribution of long-term air pollution exposure to mortality (all-cause [excluding accidents], cardiovascular and respiratory mortality).…”
Section: Longitudinal Approaches To Examining Health and Place Acromentioning
confidence: 99%
“…Hansell et al. (), for example, combined data from members of the England and Wales Longitudinal Study with data on air pollution concentrations at residence in 1971, 1981, 1991 and 2001 to examine the contribution of long‐term air pollution exposure to mortality (all‐cause [excluding accidents], cardiovascular and respiratory mortality). The authors found that associations with air pollution persisted decades after exposure, emphasising that circumstances in earlier life can have implications for health much later in life.…”
Section: Introductionmentioning
confidence: 99%
“…In England, black smoke levels dropped from 42.7 μg/m 3 in 1971 to 11.8 μg/m 3 in 2001. 30 London's annual mean PM 2.5 has held at an around 20 μg/m 3 . Recent average PM 2.5 levels in Los Angeles are near the WHO goal at 10 μg/m 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The number of deaths has subsequently been a subject of some debate with 12,000 excess deaths and some 100,000 cases of respiratory illness being suggested. Recent work by Hansell et al [3] suggests that exposure to high air pollution concentrations carries a long-term risk to health. The smog of 1952 was a catastrophe with a very high increase in respiratory mortality and morbidity.…”
Section: Reflecting On the 195smog And The 1956 Clean Air Actmentioning
confidence: 99%